Ocean Heat Uptake Efficiency Increase Since 1970. Issue 19 (5th October 2022) - Cael, B. B.
Abstract: The ocean stores the bulk of anthropogenic heat in the Earth system. The ocean heat uptake efficiency (OHUE)–the flux of heat into the ocean per degree of global warming–is therefore a key factor in how much warming will occur in the coming decades. In climate models, OHUE is well‐characterized, tending to decrease on centennial timescales; in contrast, OHUE is not well‐constrained from Earth observations. Here OHUE and its rate of change are diagnosed from global temperature and ocean heat content records. OHUE increased over the past five decades by 0.19 ± 0.04 W/m 2 K, and was on average 0.58 ± 0.08 W/m 2 K during this period. This increase is attributed to steepening anthropogenic heat gradients in the ocean, and corresponds to several years' difference in when temperature targets such as 1.5 or 2°C are exceeded. Plain Language Summary: Human activity causes extra energy to be radiated back onto Earth's surface. Much of this extra energy accumulates in the ocean as heat. Based on records of global warming and the ocean's heat content, here it is shown that the efficiency of the transfer of this energy into the ocean has increased in recent decades. This "ocean heat uptake efficiency" is the amount of energy transferred into the ocean per degree of global warming, and has increased by roughly a third over the past five decades. This translates into several years' delay until global warming temperature targets, such as 2°C warming, are exceeded. Key Points: Ocean heat uptake efficiency (OHUE) change is estimated from ocean heat content and global mean surface temperature records There is a >99% probability that ocean heat uptake efficiency increased over the past five decades OHUE was on average 0.58 ± 0.08 W/m 2 K over this period and increased during it by 0.19 ± 0.04 W/m 2 K